Recurrent Olfactory Groove Meningioma Filling the Nasal Cavity: A Case Report and Technical Video - Mastronardi, Luciano; Corrivetti, Francesco; Bevilacqua, Pio; Roperto, Raffaelino; Sufianov, Albert (Indian Journal of Neurosurgery, 2021)
Background Meningiomas are usually benign tumors and account for 15% of the overall intracranial tumors. Less than 3% of them extend up to the sinonasal region.Case Report A 61-year-old woman, operated on for a huge olfactory meningioma 8 years before, came for progressive nasal obstruction. On physical examination, a mass that completely obliterated the right nasal passage was detected. A c.e. cranial MRI confirmed the presence of an enhancing mass completely occupying the right nostril, without intracranial extension. A biopsy of the mass revealed a meningioma (WHO grade I) and the patient was admitted to our department for the surgical removal of the endonasal recurrent tumor.Results The meningioma was approached and excised by endonasal endoscopic approach using a microdebrider and electrocautery. A linear residual of tumor was left attached to the previous anterior skull base’ vascularized galeal flap, in order to avoid a communication with the intracranial compartment and a possible cerebrospinal fluid (CSF) leak. The postoperative course was uneventful, and the patient immediately referred an improvement in breathing. A c.e. postoperative MRI confirmed the nearly total removal of tumor.Conclusions We present a video with the most relevant steps of transnasal endoscopic surgical removal of a quite rare case of a recurrent olfactory groove meningioma, completely obliterating the right nostril.
Keywords: Endoscopy; meningioma; sinonasal tract; surgery